2014
DOI: 10.3329/jafmc.v9i1.18717
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low Dose Low Molecular Weight Heparin in the Treatment of Cutaneous Lichen Planus

Abstract: Introduction: Lichen planus is a common pruritic, inflammatory disease of the skin, mucous membranes, nail and hair follicles. Low dose low molecular weight heparin is administered in the treatment of cutaneous lichen planus. Objective: The objective is to evaluate the efficacy of low dose low molecular weight heparin in the treatment of cutaneous lichen planus. Materials and Methods: An interventional study was carried out in the department of Dermatology and Venereology, Combined Military Hospital (CMH), Dha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…This study revealed that 29 subjects (78.4%) presented no side‐effects, while the remaining reported local irritation, bruises and headache. However, all these inconveniences did not require particular care as they disappeared spontaneously …”
Section: Enoxaparin Sodiummentioning
confidence: 99%
“…This study revealed that 29 subjects (78.4%) presented no side‐effects, while the remaining reported local irritation, bruises and headache. However, all these inconveniences did not require particular care as they disappeared spontaneously …”
Section: Enoxaparin Sodiummentioning
confidence: 99%
“…No recurrence of PHLP was noted in follow-ups performed over a period of 1 year. Khan et al (2014) treated cutaneous LP with enoxaparin for 6 weeks. They reported disease improvement in 26 out of 31 patients.…”
Section: Enoxaparinmentioning
confidence: 99%
“…An open-labeled, uncontrolled study treated 37 cases of cutaneous LP with 3 mg of enoxaparin once-weekly for 6 weeks. Complete remission was not observed in any of the patients and the reported side effects were local irritation, bruises and headache ( Khan et al, 2014 ). So far, only one randomized clinical trial investigated the efficacy of enoxaparin in patients with disseminated LP ( Iraji et al, 2013 ).…”
Section: Enoxaparinmentioning
confidence: 99%